توظيف بعض أبعاد استراتيجية التمكين في خلق المعرفة الجديدة : دراسة تحليلية في عينة من المصارف الاهلية في مدينة الموصل - د. معن وعدالله المعاضيدي; د. علي عبدالستار الحافظ (PROSPECTIVE RESEARCHES, 2023)
Depending on the researchers signals that refers to the possibility of the appointment of the empowerment strategy as a managerial strategy to achieve organizational goals, one of them is creating new knowledge for personal, groups, departments, then to the organization as a whole, this research aims to explore the results of the appointment of some of empowerment strategy dimensions in new knowledge creation in a sample of private banks in Mosul city. The research adopt a designed questionnaire according to some scientific references, after that the questionnaire is distributed to a sample of employees in the private banks in Mosul. The researchers used the descriptive analytical method because of its high fitness to such researchs. After adopting some descriptive and experimental statistical tools such as correlation, regression and stepwise regression under the statistical packaged (SPSS) to assure from the validity of research hypothesizes in some of private banks in Mosul city, the researchers come up with some conclusions that support the role of empowerment strategy dimensions in new knowledge creation. Moreover, the researchers recommend reinforcing the processes of knowledge and information sharing in the advanced level of trust employees in the banks under-research for its prominent role in new knowledge creation.